STUDY OF TRAFFIC DUE TO THE ECONOMIC ACTIVITY OF PALANGKA RAYA MALL - Ade Widjanarko (Lambung Mangkurat University Press, 2013)
The strategic position of Palangka Raya Mall which is located on the corner of Great Roundabout in Palangkaraya city affects traffic flow on roundabout caused by trip attraction of Palangka Raya Mall. One indicator of the traffic congestion on roundabout is the decrease in the vehicle speed. This could be caused by the limited option of access to Palangka Raya Mall. Aims ofthisstudyaretoanalyzethe impact of traffic flow due to the trip attraction of Palangka Raya Mall, and to measure the roundabout performance in addressing traffic flow caused by trip attraction of Palangka Raya Mall. This research was carried out by collecting data of traffic flow volume, studying road geometry, and studying access to Palangka Raya Mall. The collected data is then analyzed using IHCM 1997 method, and adjusted to access design of Palangkaraya Mall. First access design is a modification of access to Palangkaraya Mall from Cilik Riwut Street. Second access design is a modification of access to Palangkaraya Mall from Kinibalu Street and Cilik Riwut Street. From the results of analysis carried out based on the daily peak hours, it is obtained that the degree of saturation (DS) value for existing condition is 0.809 on circulating roadway between Yos Sudarso Street and Kinibalu Street, with Level of Service (D). Degree of saturation (DS) value for first access design is 0.887 on circulating roadway between Kinibalu Street and Cilik Riwut Street, with Level of Service (D). Degree of saturation (DS) value for second access design is 0.723 on circulating roadway between Yos Sudarso Street and Kinibalu Street, with Level of Service (C). A modification of access to Palangka Raya Mall from Kinibalu Street and Cilik Riwut Street is a good solution in addressing traffic flow caused by trip attraction of Palangka Raya Mall and improving roundabout performance.